2019
DOI: 10.3390/f10100905
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Growing Stock Volume of Eucalyptus Plantations Using 3-D Point Clouds Derived from UAV Imagery and ALS Data

Abstract: Estimating forest inventory variables is important in monitoring forest resources and mitigating climate change. In this respect, forest managers require flexible, non-destructive methods for estimating volume and biomass. High-resolution and low-cost remote sensing data are increasingly available to measure three-dimensional (3D) canopy structure and to model forest structural attributes. The main objective of this study was to evaluate and compare the individual tree volume estimates derived from high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Thereafter, it is of pivotal importance to compare different remote sensed tree biomasses through statistic indexes that facilitate comparison between datasets or models with different scales, as rRMSE and adjR 2 . Guerra-Hernandez et al [57] in P. pinea plantation gained good results in the estimation of Wa SfM in comparison to measured Wa (0.85 < adjR 2 < 0.87 and 11.44% < rRMSE < 12.59% in two different years and model approaches) while Guerra-Hernandez et al [56], in a Eucalyptus plantation, got slightly worse performances (R 2 = 0.43 and rRMSE = 20.31%). However, the current work presents lower correlation values (except in one case) and lower rRMSE (Table 6) with respect to the literature references, mainly due to orchard characteristics (uneven-aged and irregularly spaced) and fine pruning evaluation purposes with respect to growth monitoring.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thereafter, it is of pivotal importance to compare different remote sensed tree biomasses through statistic indexes that facilitate comparison between datasets or models with different scales, as rRMSE and adjR 2 . Guerra-Hernandez et al [57] in P. pinea plantation gained good results in the estimation of Wa SfM in comparison to measured Wa (0.85 < adjR 2 < 0.87 and 11.44% < rRMSE < 12.59% in two different years and model approaches) while Guerra-Hernandez et al [56], in a Eucalyptus plantation, got slightly worse performances (R 2 = 0.43 and rRMSE = 20.31%). However, the current work presents lower correlation values (except in one case) and lower rRMSE (Table 6) with respect to the literature references, mainly due to orchard characteristics (uneven-aged and irregularly spaced) and fine pruning evaluation purposes with respect to growth monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, there have already been recent studies that specifically derived individual biomass and V SfM at tree level with ITC segmentation. Among these, important references in the Mediterranean environment were represented mainly by Guerra-Hernandez et al [57] and Guerra-Hernandez et al [56], who used a fixed-wing UAV equipped with an RGB camera to evaluate (i) Wa SfM in Pinus pinea regular forest plantation (10 x m regular spaced, open canopy, fairly flat terrain, no understory) and (ii) V SfM in Eucalyptus regular forest plantation (3.7 × 2.5 m regularly spaced, steep terrain). Comparing our results with the aforementioned studies, it worth noting that the RMSE could only be compared with Guerra-Hernandez et al [57], who used the same unit (kg) and reported a value of 87.46 and 117.80 kg for 2015 and 2017, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of ht estimated in our study was similar to that found by Hentz et al [37] while estimating tree heights of a young Eucalyptus plantation using DAP-UAV data (RMSE = 0.44 m). In a 7-year-old Eucalyptus plantation, Guerra-Hernández et al [25] also observed an underestimation of individual ht values, with an RMSE and bias of 2.84 m and 2.67 m, respectively. Our results were also similar to those observed by Krause et al [44] (RMSE = 0.49 m or 2.78% and bias = 0.365 m or 2.21%), who estimated individual ht using DAP-UAV and a DTM obtained by RTK in a wild pine stand in northeastern Berlin, Germany.…”
Section: Tree Heightmentioning
confidence: 90%
“…Besides the lower costs, DAP-UAV products present similarities to LiDAR data and are generated at a higher point density in a shorter time interval [22,23]. Some studies indicate that the performance of UAV photogrammetry data is adequate for estimating the characteristics of Eucalyptus stands [24,25], thus making them a feasible alternative to forest monitoring [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Stationary laser scanning to produce high-precision 3D point clouds is particularly useful for tree stem modeling [45]. In forestry, air/space-borne laser scanning and digital aerial photogrammetry are often used for stock volume estimation [25,46]. Furthermore, different LiDAR scanning techniques are applied to develop the methods of tree leaf area estimation [20,47].…”
Section: Discussionmentioning
confidence: 99%